4CPS-192 Identifying medication history errors at hospital admission using the lund integrated medicines management model. (March 2019) - Abood, E; Eriksson, T; Al Temimi, H
Abstract : Background: An accurate medication history list is an integral part of patient assessment at hospital admission. Purpose: The objective of the study was to describe the frequency, type and predictors of unintentional medication errors and to evaluate the quality of the clinical pharmacy services, focusing on the acceptance of the recommendations made by the clinical pharmacist. Material and methods: A descriptive study was conducted at two internal medicine wards at a teaching hospital using Lund Integrated Medicines Management (LIMM)-based medication reconciliation. The study pharmacist conducted medication interviews for patients shortly after hospital admission to obtain the most accurate pre-admission medication history list. This list was compared with the medication list in the patient's medical chart. Intended addition, withdrawal of a drug, or changes to the dose/dosage form in the patient's medical list was considered as medication discrepancies. However, medication discrepancies were considered as medication errors based on no identified clinical reason. Results: A total of 114 patients were included in this study. Over two-thirds of the study patients (73.6%) experienced 215 medication errors identified by a clinical pharmacist conducting medication reconciliation. Most errors were omission (87.9%). Cardiovascular agents followed by NSAID were commonly in error (53%) and (10.2%) respectively. In a logistic regression model, age (OR, 1.055: 95% CI: 1.010 to 1.102), female gender (OR, 3.468: 95% CI: 1.232 to 9.761) and number of medications at admission (OR, 0.810: 95% CI: 0.681 to 0.963) were predictors for medication history errors at admission. Conclusion: Medication errors at the time of hospital admission are common and undetected. A structured approach such as LIMM-based medication reconciliation at the hospital is needed to detect these errors. References and/or acknowledgements: Eriksson T, et al. The hospital LIMM- based clinical pharmacy service improves the quality of patient medication process and save time. Eur J Hosp Pharm 2012;19:375–2. Hellstrom LM, et al. Impact of the Lund Integrated Medicines Management (LIMM) model on medication appropriateness and drug-related hospital revisits . Eur J Clin Pharmacol 2011;67:741–52. The author would like to thank Tommy Eriksson for his permission to use the LIMM-model as a tool in conducting the study. Conflict of interest: Corporate-sponsored research or other substantive relationships: The study was supported, in part, by a grant from the Swedish Pharmaceutical Society, which is a non-profit organisation aimed at providing support for pharmaceutical research and education. The funding source had no role in the design and conduct of the study.